Dependência do automóvel, planejamento urbano e a cidade de Brasília - Vicente Correia Lima Neto; Anamaria de Arag\~ao Costa Martins (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This article presents a theoretical approach towards the relation between transportation and urban form, explaining the main principles used in the regional planning during the first half of XX century, that influenced several metropolitan areas. Taking the case of Brasilia, it is exemplified how those planning principles oriented the spatial organization of the territory. The article demonstrates the effects of decentralization in the crescent dependence on private transportation, revealing the main commuting problems in the Federal Capital of Brazil.
Keywords: O18; R38; R52; 330; urban and Regional planning; commuting; Brasilia urban design